2014
DOI: 10.1037/a0036887
|View full text |Cite
|
Sign up to set email alerts
|

A two-site randomized clinical trial of integrated psychosocial treatment for ADHD-inattentive type.

Abstract: Objective This study evaluated the efficacy of the Child Life and Attention Skills (CLAS) program, a behavioral psychosocial treatment integrated across home and school, for youth with Attention Deficit Hyperactivity Disorder-Inattentive Type (ADHD-I). Method In a two-site randomized controlled trial, 199 children (ages 7-11) were randomized to CLAS (N=74), parent-focused treatment (PFT, N=74), or treatment as usual (TAU, N=51). We compared groups on parent and teacher ratings of inattention symptoms, organi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0
14

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(139 citation statements)
references
References 60 publications
2
123
0
14
Order By: Relevance
“…The substantial reduction in ADHD symptom severity is consistent with our prior study of multicomponent treatment (Child Life and Attention Skills program [CLAS] 16 ). That study found moderate effect sizes for inattention symptom reduction per parent (d=.64) and teacher (d=.7) report as compared to effect sizes in the large range per parent (d=1.05) and moderate range per teacher (d=.67) report in this study.…”
Section: School-home Treatment For Adhd 15supporting
confidence: 82%
See 3 more Smart Citations
“…The substantial reduction in ADHD symptom severity is consistent with our prior study of multicomponent treatment (Child Life and Attention Skills program [CLAS] 16 ). That study found moderate effect sizes for inattention symptom reduction per parent (d=.64) and teacher (d=.7) report as compared to effect sizes in the large range per parent (d=1.05) and moderate range per teacher (d=.67) report in this study.…”
Section: School-home Treatment For Adhd 15supporting
confidence: 82%
“…In that study, medication usage was relatively high in all groups, and the treatment was compared to a psychoeducational intervention, which may have limited the extent to which behavioral treatment would show effects beyond services already provided. Our supposition is that the coordinated components and intensity that are specific to CLAS 16 and CLS confer greater efficacy for ADHD and ODD symptom reduction. However, because both of our samples used medication infrequently, we cannot rule out the possibility that concurrent medication use would substantially reduce room for improvement of ADHD symptoms for all behavioral treatments, including ours.…”
Section: School-home Treatment For Adhd 15mentioning
confidence: 95%
See 2 more Smart Citations
“…The Collaborative Life and Attention Skills Program [93] focuses on school-related impairments for children with predominantly inattentive symptoms of ADHD. The program consists of BPT, behavioral teacher consultation with contingencies targeting attention and organizational skills, a school-home report card system, and social and cognitive skills training directly with the child.…”
Section: Cognitive and Social Skills Trainingmentioning
confidence: 99%